Bilateral Charcot Arthropathy Treated with Bolt-Beam Constructs in the Setting of Unilateral Foot Ulcers: A Report of 2 Cases. Issue 3 (July 2021) - Sims, Michael; Foropoulos, Lauren; Bettin, Clayton
Abstract : Case: Two type-2 diabetic patients presented with bilateral Charcot arthropathy with midfoot collapse and presence of foot ulcerations on one side. The ulcerated extremity in each patient was treated surgically with fusion bolt, beam, and plate constructs in the setting of open ulceration. Bilateral extremities were treated surgically and went on to bony union and wound healing. Conclusion: Charcot arthropathy with open ulcers can be managed acutely with debridement, resection of bone, and arthrodesis. Waiting for ulcers to heal before internal fixation is performed may not be necessary in all situations.